A NOTE ON THE DIFFERENTIAL REGIONAL EFFECTS OF INCOME INEQUALITY: EMPIRICAL EVIDENCE USING U.S. COUNTY‐LEVEL DATA. (19th August 2013) - Atems, Bebonchu
ABSTRACT: This note examines the correlation between income inequality and economic growth using a panel of income distribution data for 3, 109 counties of the U.S. Using the System Generalized Method of Moments (GMM) approach, we find that for the entire sample of 3, 109 counties, an increase in a county's level of inequality has a significant negative relationship with future economic growth. In reality, however, the magnitude, sign, and significance of this relationship is not necessarily uniform across all regions of the U.S., motivating the need to examine regional differentials in the relationship between inequality and growth. Consequently, we split our dataset into metropolitan and nonmetropolitan counties, into the eight Bureau of Economic Analysis regions, and into regions of different political affiliation and economic‐dependence typology. Our results show considerable heterogeneity in the relationship between inequality and growth across these regions.